Ultrahigh current efficiency of light-emitting devices based on octadecylamine-graphene quantum dots. (February 2017) - Kim, Dae Hun; Kim, Tae Whan
Abstract: Graphene quantum dots (GQDs) have currently emerged as excellent candidates for applications in GQD-based LEDs because of their potential applications in next-generation multifunctional systems. However, the numerous oxygenous functional groups and defects existing in the GQDs restrict their florescence quantum yield, resulting in a decrease in the brightness of light-emitting devices (LEDs) based on GQDs. Here, we report on solution-processed and highly-efficient LEDs that have been developed based on octadecylamine (ODA)-GQDs. In contrast with the GQDs, the number of oxygen components in the ODA-GQDs is lower due to nucleophilic substitution between the amine and the epoxy functional groups. The current and the external quantum efficiency of an LED with ODA-GQDs are 6.51 cd/A and 2.67%, respectively, this current efficiency of 6.51 cd/A being the highest among the efficiencies reported for LEDs based on GQDs. The efficiency enhancement in the LEDs with ODA-GQDs is attributed to significant improvements in the optical properties of the ODA-GQDs. The successful demonstration of this efficiency enhancement for LEDs based on ODA-GQDs indicates a potential for applications of GQD-based LEDs as next-generation real optical sources. Graphical abstract: Highlights: ODA-GQDs formed by using a safe method of synthesis are cost-effective and have eco-friendly advantages. Oxygen content of the ODA-GQDs was smaller than that of the typical GQDs due to nucleophilic substitution. LED with ODA-GQDs have the highest current efficiency among the reported LEDs based on GQDs. Current efficiency of an LED with ODA-GQDs is 6.51 cd/A. External quantum efficiency of the LEDs with ODA-GQDs is 2.67%.